Interest Rate in Pension Plan Premium Calculation - Khafsah Joebaedi; Kankan Parmikanti; Agus Supriatna; Fauzi Akhmad; Badrulfalah Badrulfalah; Nendi Suhendi Syafei (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
This research aims to analyze the relationship between the interest rate relationship is inversely proportional to the amount of the premium on the pension plan. The method used is to measure several variables, among others FSL (Future Service Liability), PVFSAL (Present Value Future Salary), PR (Pension Rate) and Premiums. Calculation, life annuity uses actuarial assumptions, one of which is the interest rate assumption, if the assumptions used are not in accordance with the actual conditions, then what happens is excessive payments or deficient payments. The interest rate has an influence in the process of calculating the defined benefit pension plan premium. Using the assumption of different interest rates (11%, 12 % and 13%), it is found that the interest rate relationship is inversely proportional to the amount of the premium. The results of this study are FSL, PVFSAL, PR and Premiums for the interest of 11%, 12% and 13% (participants aged 25 years) as follows 720,187.97; 554,000,24; 430,570.07 (FSL in Rupiah); 27,155,187.70; 24,922,770,59; 23,002,699.40 (PVFSAL in Rupiah); 2.6521; 2.2229; 1.8718 (PR in%) and 55,535.38; 46,546.85; 39,196.00 (Premiums in Rupiah)The higher the interest rate, the smaller the pension premium and vice versa.